2005
DOI: 10.1200/jco.2004.00.7138
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Risk Following Bilateral Oophorectomy in BRCA1 and BRCA2 Mutation Carriers: An International Case-Control Study

Abstract: Oophorectomy is an effective means of reducing the risk of breast cancer in carriers of BRCA1 mutations. The data suggest oophorectomy is protective in BRCA2 carriers as well, but needs to be confirmed in other studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
292
1
14

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 396 publications
(314 citation statements)
references
References 22 publications
7
292
1
14
Order By: Relevance
“…Several studies have reported that the incidence of breast cancer declines in women with BRCA1 or BRCA2 mutations following an oopohorectomy Kauff et al, 2002;Eisen et al, 2005). In the largest of these, Eisen et al (2005) performed a casecontrol study on 1439 BRCA mutation carriers with breast cancer, and 1866 matched controls without breast cancer.…”
Section: Oophorectomymentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that the incidence of breast cancer declines in women with BRCA1 or BRCA2 mutations following an oopohorectomy Kauff et al, 2002;Eisen et al, 2005). In the largest of these, Eisen et al (2005) performed a casecontrol study on 1439 BRCA mutation carriers with breast cancer, and 1866 matched controls without breast cancer.…”
Section: Oophorectomymentioning
confidence: 99%
“…In the largest of these, Eisen et al (2005) performed a casecontrol study on 1439 BRCA mutation carriers with breast cancer, and 1866 matched controls without breast cancer. Among BRCA1 mutation carriers, the risk of breast cancer among women who had an oophorectomy was decreased by 56% (OR ¼ 0.44, 95% CI: 0.29-0.66) (Eisen et al, 2005). A protective effect was observed among both BRCA1 and BRCA2 mutation carriers for 15 years following oophorectomy (OR ¼ 0.39, 95% CI: 0.26-0.57).…”
Section: Oophorectomymentioning
confidence: 99%
“…[5][6][7][8][9][10][11] Documenting family history is important for recognizing individuals who may have a predisposition to HBOC or Lynch syndrome, particularly individuals without a personal history of cancer who may have the most to gain from genetic risk assessment and resulting recommendations for risk-appropriate cancer screening and prevention. In addition, genetic testing can refine the genetic risk in high-risk families and further inform recommendations for screening and prevention, particularly when a familial mutation is known.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed review of the nongenetic risk factors is beyond the scope of this review, but it is worth reviewing briefly some of the risk factors that provided consistent evidence of association with breast cancer risk for mutation carriers across several studies. Briefly, these include parity and ⁄ or increasing number of live births, which were found to be associated with decreased breast cancer risk [76][77][78], oral contraceptive use, where there have been reports for both increased and decreased breast cancer risks associated with oral contraceptive use [79][80][81], bilateral prophylactic oophorectomy, which has been shown to be consistently protective for breast cancer risk in mutation carriers [82][83][84], and use of the chemoprevention drug tamoxifen, which has been shown to be protective for contralateral breast cancer in both BRCA1 and BRCA2 mutation carriers [86,87]. In addition, exposure to chest X-rays has been associated with increased breast cancer risks for BRCA1 and BRCA2 mutation carriers [88].…”
Section: Environmental Hormonal and Reproductive Modifiers Of Riskmentioning
confidence: 99%